Plan-Do-Review-Share-Happy (Plandoresh) as a Development Strategy for Critical Thinking of Vocational School Students - Aftoni, Aftoni; Ekohariadi, Ekohariadi; Soeryanto, Soeryanto; Agung, Achmad Imam; Saqr, Mohammed (Cita konsultindo, 2024)
The learning process and traditional teaching materials include activities that require memory and memorization. Most students are trained to follow this low-level thinking pattern in schools including vocational schools. When computers take over the routine tasks at work, a number of employees will be involved in tasks that require them to be more flexible and creative in solving problems. For this reason, the vocational school learning system must encourage students to become critical thinkers, through appropriate learning strategies. The purpose of this study was to test the validity of the Plan-Do-Review-Share-Happy (Plandoresh) strategy stages in the development for critical thinking of vocational students. This study used a descriptive method with the aim of obtaining the validity of the Plandoresh strategy stages from vocational school teachers with a random sample of 62 respondents. The results showed that: 1) Plan stage is valid with r count > r table of 0.845 > 0.254, 2) Do stage is valid with r count> r table of 0.889, 3) Review stage is valid with r count > r table of 0.866, 4) Share stage is valid with r count > r table of 0.880, 5) Happy stage is valid with r count > r table of 0.920. Based on these results, it can be concluded that the stages of the Plandores strategy are valid to be applied as a learning strategy for vocational students.